Etude et réalisation d'une machine CNC à trois axes (Gravure sur bois) - اسماعيل, فار; اسحاق, كياتي; عنتر, شكيمة (University Of El Oued, 2020)
"CNC technology has become a necessary requirement in the industrial world, and on the other hand, we are witnessing an increase in the level of marketing requirements in terms of quality, price and quantity. So the CNC machine is able to meet these demands and more than that, it has gained a prominent position as it drives the economy and production further. As we focused in this note on studying and modeling a three-axis CNC machine, which is one of the most important machines used on the public and private levels in the industry. Thus, we presented in our work some basic concepts and general structure about a CNC machine, and in the second part we presented modeling, then an engineering and kinematic study of the machine, and finally we designed the machine. Starting from scratch with Fusion 360, then we realization, and simulations using PROTEUS and we concluded the project with device testing" "أصبحت تقنية CNC من المتطلبات الضرورية في العالم الصناعي، ومن ناحية أخرى، نشهد زيادة في مستوى متطلبات التسويق من حيث الجودة والسعر والكمية، وبالتالي فإن آلة CNC قادرة على تلبية هذه المطالب وأكثر من ذلك، فقد اكتسبت مكانة بارزة ألنها تقود عجلة االقتصاد واإلنتاج إلى أبعد حد، حيث ركزنا في هذه المذكرة على دراسة ونمذجة آلة CNC ذات ثالثة محاور والتي تعد من أهم اآلالت المستخدمة على المستويين العام والخاص في الصناعة وهكذا قدمنا في عملنا بعض المفاهيم األساسية والهيكل عام حول ماكينة CNC وفي الجزء الثاني قدمنا نمذجة ثم دراسة قمنا بتصميم اآللة. ابتداء من الصفر بهندسية وحركية لآللة، وأخيرا استخدام برنامج 360 Fusion ثم تحقيق المكنة، وتنفيذ ًعمليات المحاكاة باستخدام برنامج PROTEUS واختتمنا المشروع باختبار الجهاز"
Electromécanique مذكرة ماستر تخصص
Keywords: Machine CNC, Numerical control, Stepper Motor, Grbl, G-code; مكنة ت ع ح، التحكم العددي، محرك خطوة بخطوة، ج ر ب ل، ج-كود